Health- and skill-related physical fitness in Costa Rican special operations police units - Cervantes-Sanabria, Jorge (2025)
The aims of this study were: a) to provide a detailed health- and skill-related physical fitness profile of a cohort of Costa Rican Special Operations Police (SOP) units and b) to compare selected physical measures by age groups: body weight, body mass index (BMI), fat mass, body fat percentage, lean mass, resting heart rate, blood pressure, grip strength, flexibility, vertical jump height, muscular resistance, agility, anaerobic resistance and cardiorespiratory capacity were measured in SOP active members. Seventy-nine officers (age = 37.68 ± 7.86 years, height = 172.58 ± 5.35 cm, body weight = 80.49 ± 10.69 kg, BMI = 27.05 ± 3.34 kg∙m-2) participated in the study. Health- and skill-related physical fitness results of the participants were sub-optimal. Statistically significant differences were observed between age subgroups in lean mass in kg (F = 6.581, p = 0.002), A/G ratio (F = 10.078, p = 0.000), right- and left-hand grip (F = 5.680, p = 0.005; F = 8.386, p = 0.001), vertical jump (SQJ , F = 8.047, p = 0.001; CMJ , F = 8.167, p = 0.001), muscular resistance (F = 4.063, p = 0.021), agility (F = 9.055, p = 0.000), anaerobic resistance (F = 7.572, p = 0.001), and cardiorespiratory capacity (F = 5.034, p = 0.009). Police officers should review their strength and conditioning programs because their fitness profile is currently below general fitness standards. Age was shown to be an important factor in SOP units’ strength and conditioning performance.